tìm x
( 2x - 1 ) 5 - 27 x ( 2x - 1 ) 2 = 0
ai giải giùm mk cái
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,=x^2-1-\left(x^2+4x+4\right)=x^2-1-x^2-4x-4=11\)
\(\Leftrightarrow-5x=15\)
\(\Leftrightarrow x=-3\)
Vậy ...
\(b,=\left(x-3-2x+5\right)\left(x-3+2x-5\right)=0\)
\(\Leftrightarrow\left(-x+2\right)\left(3x-8\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{8}{3}\end{matrix}\right.\)
Vậy ...
a) \(\left(x-1\right)\left(x+1\right)-\left(x+2\right)^2=11\)
\(\Rightarrow x^2-1-x^2-4x-4-11=0\)
=> -4x - 16 = 0
=> -4x = 16
=> x = -4
b) \(\left(x-3\right)^2-\left(2x-5\right)^2=0\)
=> (x - 3 + 2x - 5).(x - 3 - 2x + 5) = 0
=> (3x - 8).(-x + 2) = 0
=> x = 8/3 hoặc x = 2
a) \(3\left(2x-5\right)+125=134\)
\(\Leftrightarrow3\left(2x-5\right)=9\)
\(\Leftrightarrow2x-5=3\)
\(\Leftrightarrow2x=8\Leftrightarrow x=4\)
b) \(\left(2x+5\right)+\left(2x+3\right)+\left(2x+1\right)=27\)
\(\Leftrightarrow6x+9=27\)
\(\Leftrightarrow6x=18\Leftrightarrow x=3\)
d) \(27\left(x-27\right)-27=0\)
\(\Leftrightarrow27\left(x-27\right)=27\)
\(\Leftrightarrow x-27=1\Leftrightarrow x=28\)
\(\left(2x-1\right)^3=27\)
\(\left(2x-1\right)^3=3^3\)
\(2x-1=3\)
\(2x=3+1=4\)
\(x=4:2\)
\(x=2\)
\(5\left(x+3\right)-2x\left(x+3\right)=0\)
<=> \(\left(5-2x\right)\left(x+3\right)=0\)
<=> \(\hept{\begin{cases}5-2x=0\\x+3=0\end{cases}}\)
<=> \(\hept{\begin{cases}x=\frac{5}{2}\\x=-3\end{cases}}\)
\(4x\left(x-2018\right)-x+2018=0\)
<=> \(4x\left(x-2018\right)-\left(x-2018\right)=0\)
<=> \(\left(4x-1\right)\left(x-2018\right)=0\)
<=> \(\hept{\begin{cases}4x-1=0\\x-2018=0\end{cases}}\)
<=> \(\hept{\begin{cases}x=\frac{1}{4}\\x=2018\end{cases}}\)
\(\left(x+1\right)^2-\left(x+1\right)=0\)
<=> \(\left(x+1\right)\left(x+1-1\right)=0\)
<=> \(\left(x+1\right).x=0\)
<=> \(\hept{\begin{cases}x=0\\x+1=0\end{cases}}\)
<=> \(\hept{\begin{cases}x=0\\x=-1\end{cases}}\)
học tốt
a) \(5\left(x+3\right)-2x\left(3+x\right)=0\)
\(5\left(x+3\right)+2x\left(x+3\right)=0\)
\(\left(x+3\right)\left(5+2x\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+3=0\\5+2x=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-3\\x=\frac{-5}{2}\end{cases}}\)
b) \(4x\left(x-2018\right)-x+2018=0\)
\(4x\left(x-2018\right)-\left(x-2018\right)=0\)
\(\left(x-2018\right)\left(4x-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-2018=0\\4x-1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=2018\\x=\frac{1}{4}\end{cases}}\)
c) \(\left(x+1\right)^2-\left(x+1\right)=0\)
\(\left(x+1\right)\left(x+1-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+1=0\\x+1-1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-1\\x=0\end{cases}}\)
a) (426 + x) : 5 = 120
(=) 426 + x = 120 :5
(=) 426 + x = 24
(=) x = 24 - 426
(=) x = - 402
Vậy x = - 402
b) 5844 : x -159 = 328
(=) 5844 : x = 328+ 159
(=) 5844 : x = 487
(=) x = 5844 : 487
(=) x = 12
Vậy x = 12
c) 32x + 1 = 27
(=) 32x = 27 -1
(=) 32x = 26
=> vô lý
vậy x thuộc tập hợp rỗng
d) (3x - 1)2 = 64
(=) (3x - 1)2 = 82
(=) 3x - 1 = 8
(=) 3x = 8 + 1
(=) 3x = 9
(=) x = 9 : 3
(=) x = 3
Vậy x = 3
( 426 + x ) : 5 = 120
( 426 + x ) = 600
x = 600 - 426
x = 174
b ) 5844 : x - 159 = 328
5844 : x = 328 + 159
5844 : x = 487
x = 5844 : 487
x = 12
d ) ( 3x - 1 ) 2 = 64
( 3x - 1 ) = 8
3x = 9
x = 3